Size design and nonlinear stress-strain relationship of parallel bamboo strand lumbers in tension and compression. (October 2022) - Zhu, Wenli; Qiu, Zhenyu; Zhou, Jiannan; Jin, Fengnian; Fan, Hualin
Graphical abstract: Highlights: Specimen size design of parallel bamboo strand lumbers in tension and compression were revealed. Reasonable sample dimension was suggested for parallel bamboo strand lumbers. The most suitable stress-strain model was suggested for parallel bamboo strand lumbers. Abstract: Based on the current national test standard of wood structures (China), tensile specimens with different section thickness and effective length were designed to investigate the size design on the tensile property of the parallel bamboo strand lumber (PBSL). At the same time, compression components with different length were designed to study the effect of slenderness ratio on the compression performance of the PBSL. Four nonlinear constitutive models were applied to model the compressive stress-strain curves. The results show that the tensile property of the PBSL is tightly related to the section thickness. It is recommended that section thickness of 10 mm and effective length of 60 mm might be the most appropriate specimen size for the tensile experiment. The compressive strength increases with reducing the slenderness ratio. Among the four nonlinear constitutive models, the Ramberg-Osgood relationship could most consistently fit the compression stress-strain relationship of the PBSL.